ANALISIS TERHADAP SUAMI YANG TIDAK MEMBERIKAN NAFKAH KEPADA ISTRI KARIR ( PRESPEKTIF HUKUM ISLAM DAN HUKUM POSITIF) - Annisaa Ningrum Abdillah; Khoirul Asfiyak; Dwi Ari Kurniawati (Jurnal Hikmatina, 2021)
The marriage relationship between husband and wife will give rise to rights and obligations in both. In Islamic Law and Positive Law has been set about how these rights and obligations are clearly and in detail. One of the things that makes a husband's duty is about living. In the household, a husband is obliged to provide for his wife and family in the form of clothing, boards, and food. From time to time, there are many wives who work and even have a greater income than the husband so the problem arises whether the husband is still obliged to provide for the wife's career. Such questions will be discussed in this study. This research uses the library method by utilizing library resources to obtain research data. The results of this study concluded that husbands are still obliged to provide for wives even if the wife's career. And the husband and wife have their own rights and obligations that have been stipulated in the Positive Law and Islamic Law.Keywords: living, wife career, islamic law, positive law